Dooshi visha (Cumulative Toxicity) & Its Management: An Ayurvedic View - Sharma, Monika; Sharma, Anita; Sharma, Charu (International Research Journal of Ayurveda & Yoga, 2020)
Visha causes concern to all living beings by making the organism grievously ill in its functioning & leading to death in certain cases. It creates depression and sorrow in body and mind. Acharya Sushruta has stated that a part of Sthavar (Inanimate), Jangam (Animate) or Kritrim (Artificial) poison, which accumulated and cannot be excreted from body completely due to its chronic and cumulative nature or becomes less potent after digestion or counter action of antidotes & stays in the body for a prolong period and vitiating the body slowly is called Dooshi Visha. In current era there are so many poisonous materials has been available which have such a nature of accumulations within the body are prolonged periods. Metals and metallic compounds, Pesticides and some food additives have found a nature of accumulations within the living body when it exposed since prolonged period persistent. In this study management of cumulative Poison with special reference to Dooshi Visha has discussed.